The Challenges of National e-ID for Kurdistan Region government for Multi-purposes (International Journal of Engineering and Computer Science, 2015)
Kurdistan in Iraq  is a non industrial region in in Iraq. Since 1992, Kurdistan parliament has declared some rules and regulating in diverse areas omit Assemblage technologies and bearing electronics scheme.  The National E-ID project brings an optimized frequent platform for Carpet Region Authorities to interact with varied authorities, agencies and transact electronically, and has been set up to promote comprehensive citizenship, impelling governance, the cashless action and efficient ontogeny. With the integration of driver’s license, voter registration, health insurance, tax and pensions into one platform, the project is expected to transform both the way the government interacts with the public and the future development of Kurdistan Region Iraq KRI. The National e-ID project has been brought in to address these issues. The need for a trusted identity system has also been fuelled by such factors as the growing threat of kidnappings and terrorist attacks, rapid growth in the telecoms industry, the population is declining inclination to travel long distances to access government services, and the recent government policy shift towards a cashless economy with a focus on information and communication technologies. Since 2010 this project has been announced, it but till this moment it does not apply yet. A core element of the project is the new multi-purpose e-ID card combining several applications, including MasterCard’s prepaid payment technology and Cryptovision’s biometric identification technology using Public Key Infrastructure. This study tries to investigate similar E-national ID system and shows signs of this project as a starting point of E-Government and how it can be integrated into other public and private services to save time and money for our KRI citizens, adding more give a general recommendation  for future usage of this system.